2016
DOI: 10.1902/jop.2016.160102
|View full text |Cite|
|
Sign up to set email alerts
|

Macrophages Play a Key Role in the Obesity‐Induced Periodontal Innate Immune Dysfunction via Nucleotide‐Binding Oligomerization Domain‐Like Receptor Protein 3 Pathway

Abstract: Obesity may paralyze innate immune response of periodontium via attenuating infiltration and activation of macrophages and further aggravate periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 43 publications
2
35
1
Order By: Relevance
“…To investigate the possible interaction between periodontitis and chronic kidney disease in obesity, we induced periodontitis in mice of the high-fat diet-induced obesity (DIO) and control (low-fat diet) groups as reported in the previous studies (13,14). We observed whether the high-fat diet or periodontitis affected the levels of serum proteins as serum indicators of renal function (Table 1), and then we performed Student-Newman-Keuls (SNK) method for multiple comparisons.…”
Section: The High-fat Diet But Not Periodontitis Affects the Levels Omentioning
confidence: 99%
“…To investigate the possible interaction between periodontitis and chronic kidney disease in obesity, we induced periodontitis in mice of the high-fat diet-induced obesity (DIO) and control (low-fat diet) groups as reported in the previous studies (13,14). We observed whether the high-fat diet or periodontitis affected the levels of serum proteins as serum indicators of renal function (Table 1), and then we performed Student-Newman-Keuls (SNK) method for multiple comparisons.…”
Section: The High-fat Diet But Not Periodontitis Affects the Levels Omentioning
confidence: 99%
“…Obesity is a chronic inflammatory condition with worldwide prevalence, and numerous studies have described the impact of obesity in the pathophysiology of periodontal disease. Studies have reported that obesity is associated with greater prevalence and severity of disease aaa(Gorman, Kaye, Apovian, et al., ; Gorman, Kaye, Nunn, & Garcia, ; Jimenez, Hu, Marino, Li, & Joshipura, ; Linden, Patterson, Evans, & Kee, ), while mechanistic studies have revealed that macrophages exposed to a hyperlipidemic environment display altered functional capacity including reduced infiltration, activation and phagocytic capacity (Huang et al., ), defective oxidative burst (Lee et al., ; Mancuso et al., ) and decreased macrophage cytokine production (Chu et al., ; Doxey et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…infiltration, activation and phagocytic capacity (Huang et al, 2012), defective oxidative burst (Lee et al, 1999;Mancuso et al, 2002) and decreased macrophage cytokine production (Chu et al, 1999;Doxey et al, 1998).…”
mentioning
confidence: 99%
“…77 Obesity also may abate the innate immune response in the periodontium, for example via attenuation of macrophage infiltration and activation. 78 This may explain the higher occurrence of spontaneous 79 and ligature-induced 80 periodontal breakdown in obese experimental animals.…”
Section: Ta B L E 4 (Continued)mentioning
confidence: 99%